Enhancement of Butanol Production Efficiency from Sweet Sorghum Stem Juice by Clostridium beijerinckii Using Statistical Experimental Design - Likit Sirisantimethakom (Science Faculty of Chiang Mai University, 2019)
Factors involving in butanol production, i.e., initial pH, inoculum size, as well as the levels of some chemicals were investigated for their effects on butanol production from sweet sorghum stem juice (60 g/L of total sugar) by Clostridium beijerinckii TISTR 1461 using a Plackett-Burman design. Only CaCO3, (NH4)2SO4 and butyric acid showed significant effects on butanol production. Then, batch fermentation experiments employing response surface methodology (RSM) with Box-Behnken design were performed to determine the optimal concentrations of these components. The statistical analyses revealed that the optimal concentrations giving the maximal butanol production were 7.14 g/L of CaCO3, 1.27 g/L of (NH4)2SO4 and 5.18 g/L of butyric acid. A model of butanol production was developed with an R2 value of 0.975. Verification experiments in a 2-L fermenter under the optimal conditions gave satisfactory results for butanol concentration (16.91 g/L) and productivity (0.47 g/L/h).